Performance of A1, A2, A3, A4(M), A4(G) and A4(VZM) cytoplasms based iso-nuclear sorghum hybrids for shoot fly resistance across-rainy and post-rainy seasons - Reddy, P. Sanjana; Reddy, B.V.S.; Kumar, A. Ashok; Sharma, H.C. (The Indian Journal of Genetics and Plant Breeding, 2016)
Breeding for resistance to sorghum shoot fly in A1 CMS system has been only partially successful. To compare the alternate Cytoplasmic Male Sterility (CMS) systems for shoot fly resistance, 72 hybrids produced by crossing 36 A-lines carrying six diverse cytoplasms namely, A1, A2, A3, A 4(M), A4(G), A4(VZM), each in six nuclear backgrounds with two common fertility restorers. The hybrids were evaluated during 2006 and 2007 rainy and post rainy seasons in shoot fly screening trials at ICRISAT. ANOVA indicated absence of overall cytoplasmic influence on dead hearts%. The general (GCA) and specific combining ability (SCA) estimates suggested that inheritance for deadhearts was governed by additive-type of gene action. For GCA effects, the A2 and A4(M) cytoplasms and for SCA effects, the A4(G) and A 4(M) cytoplasms were superior over other cytoplasms. Overall, the A4(M)cytoplasm seemed to contribute to shoot fly resistance in hybrid combinations. However, use of all the six alternate cytoplasms should not increase the risk of shoot fly in commercial grain production.